Spectroscopic determination of temperature distributions for a TIG arc - Thornton, M. F. (Cranfield University, 1993)
Argon TIG arc temperatures have been measured for a wide range of arc parameters using the 'Fowler-Milne' spectroscopic method. Prompted by widespread disagreement amongst temperatures published by previous groups, a detailed investigation has been carried out into those experimental and theoretical aspects of the measurement process that may have led to incorrect results. The tests have included the variation of experimental parameters, the choice of Abel inversion procedure, and the calculation of argon species number densities and partition functions. The existence of equilibrium within the TIG arc has been investigated by determining temperatures with a number of argon emission lines. Significant differences 'in derived values of the temperatures were observed within 1mm of the tungsten cathode tip, smaller variations were observed over the remainder of the arc. The results indicate that large scale departures from a Boltzmann distribution amongst argon atom excited states exists close to the tungsten tip, deviations decrease with increasing distance from the tip but do not disappear completely. lt is believed that the breakdown of equilibrium within the argon TIG arc may help to explain the disagreement in temperatures obtained by past groups that have used spectroscopic methods. Despite evidence for non-equilibrium within the arc. results from previous groups suggest that derived values of .the temperatures are substantially correct in the main body of the arc. The detailed temperature maps provide useful information on temperature changes with arc parameters for the purposes of modelling and understanding of the arc.